The role of [η2-bis(tert-butylsulfonyl)acetylene](carbonyl)(η5-cyclopentadienyl)cobalt(I) as an intermediate in the alkyne dimerisation - Stäb, Tobias; Chávez, Jorge A.; Gleiter, Rolf; Nuber, Bernhard (European journal of inorganic chemistry, 2005)
Dicarbonyl(η5-cyclopentadienyl)cobalt(I) (1) reacts with the electron-poor alkyne bis(tert-butylsulfonyl)acetylene to give the corresponding cyclobutadiene complex 6, whereas the reaction of [CpCo(CO)2] with dimethyl acetylenedicarboxylate yields the cyclopentadienone complex 7 under the same conditions. The cyclobutadiene complex 6 could not be obtained by the treatment of [η2-bis(tert-butylsulfonyl)acetylene](carbonyl)(η5-cyclopentadienyl)cobalt(I) [3(H)] with an excess of bis(tert-butylsulfonyl)acetylene. The same holds for the treatment of 3(H) with dimethyl acetylenedicarboxylate and bis(catecholatoboryl)acetylene. With these results we assume that the monoalkyne complex 3(H) is not an intermediate in the alkyne oligomerisation of electron-poor alkynes, as was shown for electron-rich ones. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2005)
Dedicated to Prof. Dr. Günter Helmchen on the occasion of his 65th birthday
Im Titel erscheinen die Ziffern 2 und 5 hochgestellt
Gesehen am 23.10.2020
Keywords: Festschrift